Design of blueberry anthocyanin/TiO2 composite layer-based photoanode and N-doped porous blueberry-derived carbon-loaded Ni nanoparticle-based counter electrode for dye-sensitized solar cells. Issue 11 (6th March 2023) - Qin, Xiang; Liu, Jingjing; Teng, Genhui; Liu, Baorui; Xie, Yanhui; Ma, Lin; Hu, Dongying
Abstract : In this study, we have creatively designed photoanode and counter electrodes materials with blueberries as the key performance improvement, and verified the contribution of blueberry to the photoelectric conversion performance of DSSCs. Abstract : P25/PBP (TiO2, anthocyanins) prepared by combining PBP (blueberry peels) with P25, and N-doped porous carbon-supported Ni nanoparticles (Ni@NPC- X ) prepared using blueberry-derived carbon were used for the application as photoanode and the counter electrode, respectively, in dye-sensitized solar cells (DSSCs) to create a new perspective for blueberry-based photo-powered energy systems. PBP was introduced into the P25 photoanode and carbonized to form a C-like structure after annealing that improved its adsorption capacity for N719 dye, contributing a 17.3% higher power conversion efficiency (PCE) of P25/PBP-Pt (5.82%) than that of P25-Pt (4.96%). The structure of the porous carbon changes from a flat surface to a petal-like structure due to the N doping by melamine, and the specific surface area increases. N-doped three-dimensional porous carbon supported the loading and reduced the agglomeration of Ni nanoparticles, reducing the charge transfer resistance, and providing a fast electron transfer path. The doping of Ni and N on the porous carbon worked synergistically to enhance the electrocatalytic activity of the Ni@NPC- X electrode. The PCE of the DSSCs assembled by Ni@NPC-1.5 and P25/PBP was 4.86%. Also, the Ni@NPC-1.5 electrode exhibited 116.12 F g −1 and a capacitance retention rate of 98.2% (10 000 cycles), further confirming good electrocatalysis and cycle stability.